Analyse Economique De La Restauration Des Aires Protegees En Côte D’ivoire : Cas Du Parc National De Taï - Moussa Sangare (European Scientific Journal, ESJ, 2017)
This paper analyses the optimal conditions of the imperative restoration of the National Park of Tai. Particularly, it aims to study, using the contingent valuation method, the feasibility of a voluntary retrocession of agricultural parcels located in the vicinity of this park. Thus a simple censored tobit model is used to identify the determinants of willingness to accept of smallholders. Data collection was conducted among 508 households settled in the neighboring localities of this park. Statistical analysis of survey data reveals initially the unpopularity and difficulties of implementing such a measure given the low commitment of smallholders to the proposed policy. Secondly, econometric analysis identifies the instruction attainment, part-time practice of farming, membership in some support group, previous farming experience, the extend of ceded parcel, farm-home distance and environmental sensitivity of the individual like the main explicative variables of the willingness to accept of smallholders.